2013
DOI: 10.1007/s00005-013-0243-0
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors’ Pathway Disturbances are Associated with Increased Susceptibility to Infections in Humans

Abstract: Toll-like receptors (TLRs) sense microbial products and play an important role in innate immunity. Currently, 11 members of TLRs have been identified in humans, with important function in host defense in early steps of the inflammatory response. TLRs are present in the plasma membrane (TLR1, TLR2, TLR4, TLR5, TLR6) and endosome (TLR3, TLR7, TLR8, TLR9) of leukocytes. TLRs and IL-1R are a family of receptors related to the innate immune response that contain an intracellular domain known as the Toll-IL-1R (TIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 175 publications
0
57
1
2
Order By: Relevance
“…The TIR domain consists of three boxes of conserved residues set in a core sequence of 135-160 amino acids, which facilitate receptor-adaptor oligomerization 14 . The differential recruitment of these adaptor proteins results in the formation of a myddosome complex-an oligomeric signaling complex that consists of the adaptor proteins MyD88, IRAK1 and IRAK4-and activation of various signaling molecules, such as NFκB, MAPK, and interferon regulatory factor (IRF) and the subsequent production and release of various cytokines and chemokines ( Figure 1; Table 1) [15][16][17][18][19] .…”
Section: [H1] Prrs Of the Innate Immune System [H2] Toll-like Receptorsmentioning
confidence: 99%
“…The TIR domain consists of three boxes of conserved residues set in a core sequence of 135-160 amino acids, which facilitate receptor-adaptor oligomerization 14 . The differential recruitment of these adaptor proteins results in the formation of a myddosome complex-an oligomeric signaling complex that consists of the adaptor proteins MyD88, IRAK1 and IRAK4-and activation of various signaling molecules, such as NFκB, MAPK, and interferon regulatory factor (IRF) and the subsequent production and release of various cytokines and chemokines ( Figure 1; Table 1) [15][16][17][18][19] .…”
Section: [H1] Prrs Of the Innate Immune System [H2] Toll-like Receptorsmentioning
confidence: 99%
“…Our study showed a significant association between the presence of these two polymorphisms with a lower inflammatory grade in ESRD patients under HD. TLR4 is the primary receptor for lipopolysaccharide (LPS) from Gram-negative bacteria, but it also recognizes fungal mannan, parasitic phospholipids, viral envelop proteins and host heat shock proteins (12). The TLR4 polymorphism c.896A>G has been studied and it was related to an increased susceptibility to Gram-negative bacteremia and septic shock (16,17), by reducing LPS responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…TLR targeted drugs have been approved and small-molecule compounds are being investigated in the treatment of viral infections (29). However, therapeutic modulation by TLRs could cause unexpected unsafe responses that could be avoided with an accurate knowledge about each TLR in the pathophysiology of several diseases (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, treatment with the TNFblocking antibody, "infl iximab," indicates good clinical response to anti-TNF-alpha agents. This is accompanied with reduced IDO expression (Wolf et al 2004 ;Frazão et al 2013 ).…”
Section: Chronic Immune Activation In Infl Ammatory and Functional Bomentioning
confidence: 91%